2016
DOI: 10.1371/journal.pone.0157799
|View full text |Cite
|
Sign up to set email alerts
|

Enterobactin as Part of the Oxidative Stress Response Repertoire

Abstract: Microorganisms produce siderophores to facilitate iron uptake and even though this trait has been extensively studied, there is growing evidence suggesting that siderophores may have other physiological roles aside from iron acquisition. In support of this notion, we previously linked the archetypal siderophore enterobactin with oxidative stress alleviation. To further characterize this association, we studied the sensitivity of Escherichia coli strains lacking different components of the enterobactin system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
82
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 45 publications
(70 reference statements)
4
82
1
1
Order By: Relevance
“…Accordingly, it was presumed that Ent may exert a plethora of key physiological functions that could account for its high metabolic cost (38), aside from acquiring iron to support bacterial growth. Such notion has been demonstrated in studies whereby Ent was shown to be fundamental for E. coli to establish colonization in the mammalian gut (39), develop mature biofilms (40, 41), alleviate oxidative stress (42, 43), and neutralize the anti-microbial activity of MPO (21). The multifaceted property of Ent is further exemplified by our findings that it could inhibit an array of neutrophil functions, including ROS generation, NETs formation, degranulation, phagocytosis and bacterial killing activity.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, it was presumed that Ent may exert a plethora of key physiological functions that could account for its high metabolic cost (38), aside from acquiring iron to support bacterial growth. Such notion has been demonstrated in studies whereby Ent was shown to be fundamental for E. coli to establish colonization in the mammalian gut (39), develop mature biofilms (40, 41), alleviate oxidative stress (42, 43), and neutralize the anti-microbial activity of MPO (21). The multifaceted property of Ent is further exemplified by our findings that it could inhibit an array of neutrophil functions, including ROS generation, NETs formation, degranulation, phagocytosis and bacterial killing activity.…”
Section: Discussionmentioning
confidence: 95%
“…In previous study, it was reported that in acidic medium 2,3-dihydroxybenzoic acid (DHB), a phenolic compound consisting of catechol group which absorbs below 330 nm showing two absorption bands with maxima at 254 nm and 292 nm, respectively (Iglesias et al, 2011). DHB is an intermediate involved in the synthesis of catecholate type siderophore (Peralta et al, 2016). These evidences support the presence of DHB in LJH19 grown supernatant indicating the production of catecholate type siderophore.…”
Section: Resultsmentioning
confidence: 99%
“…, enterobactin and salmochelin) are protective against reactive oxygen species (35, 50–55). This protection is not due to iron sequestration that prevents additional Fenton reactions but is a function of the antioxidant properties of catechols (50, 53). Supplementation with free catechols doesn’t rescue the protective function of enterobactin, which requires import and hydrolysis for effective oxidative stress protection (53, 54).…”
Section: Discussionmentioning
confidence: 99%
“…This protection is not due to iron sequestration that prevents additional Fenton reactions but is a function of the antioxidant properties of catechols (50, 53). Supplementation with free catechols doesn’t rescue the protective function of enterobactin, which requires import and hydrolysis for effective oxidative stress protection (53, 54). It is unclear whether petrobactin requires additional processing to become active against oxidative stress, though the detection of petrobactin associated with spores by mass spectrometry suggests it does not.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation